The Role of Success Rate, Discovery, Appraisal Spending, and Transitioning Region on Exploration Drilling of Oil and Gas in Indonesia in 2004–2015 - Harry Patria (Institute for Economic and Social Research, 2021)
Petroleum exploration decision remains a subject of petroleum and economic studies for decades. Most of the studies discuss the investment decision by focusing on either a technical or economic perspective. In reality, economic, geological, and environmental factors are expected to determine the way investors make a decision. This study aims to increase the understanding of best practices in decision-making by scrutinizing integrative perspectives applying panel data of 32 basins in Indonesia in 2004–2015. This study provides several contributions to optimize decisions on wells drilled. First, this study derives an empirical model examining several plausible factors of economy, geology, and environment. Second, the findings demonstrate how to empirically examine which factors significantly determine wells drilled by companies. The last contribution is to empirically support a technical transformation from Western to Eastern exploration due to the natural depletion of oil fields.